Brugia malayi microfilariae induce a regulatory monocyte/macrophage phenotype that suppresses innate and adaptive immune responses. - Noëlle Louise O'Regan; Svenja Steinfelder; Gopinath Venugopal; Gopala B Rao; Richard Lucius; Aparna Srikantam; Susanne Hartmann (Public Library of Science (PLoS), 2014)
Monocytes and macrophages contribute to the dysfunction of immune responses in human filariasis. During patent infection monocytes encounter microfilariae in the blood, an event that occurs in asymptomatically infected filariasis patients that are immunologically hyporeactive.To determine whether blood microfilariae directly act on blood monocytes and in vitro generated macrophages to induce a regulatory phenotype that interferes with innate and adaptive responses.Monocytes and in vitro generated macrophages from filaria non-endemic normal donors were stimulated in vitro with Brugia malayi microfilarial (Mf) lysate. We could show that monocytes stimulated with Mf lysate develop a defined regulatory phenotype, characterised by expression of the immunoregulatory markers IL-10 and PD-L1. Significantly, this regulatory phenotype was recapitulated in monocytes from Wuchereria bancrofti asymptomatically infected patients but not patients with pathology or endemic normals. Monocytes from non-endemic donors stimulated with Mf lysate directly inhibited CD4+ T cell proliferation and cytokine production (IFN-γ, IL-13 and IL-10). IFN-γ responses were restored by neutralising IL-10 or PD-1. Furthermore, macrophages stimulated with Mf lysate expressed high levels of IL-10 and had suppressed phagocytic abilities. Finally Mf lysate applied during the differentiation of macrophages in vitro interfered with macrophage abilities to respond to subsequent LPS stimulation in a selective manner.Conclusively, our study demonstrates that Mf lysate stimulation of monocytes from healthy donors in vitro induces a regulatory phenotype, characterized by expression of PD-L1 and IL-10. This phenotype is directly reflected in monocytes from filarial patients with asymptomatic infection but not patients with pathology or endemic normals. We suggest that suppression of T cell functions typically seen in lymphatic filariasis is caused by microfilaria-modulated monocytes in an IL-10-dependent manner. Together with suppression of macrophage innate responses, this may contribute to the overall down-regulation of immune responses observed in asymptomatically infected patients.